The Smart Safeguard System for COVID-19 to prevent cluster-infection in workplaces. Issue 8 (August 2021) - Li, Ziyi; Li, Guowei; He, Jingjun; Cao, Donglin; Tian, Junzhang
Abstract: The ongoing Coronavirus Disease 2019 (COVID-19) broke out in China since December 2019, and rapidly spread worldwide. To contain the disease, unessential businesses had been shut down in several countries to a varying extent. Nowadays, the enterprises are resuming productions and businesses. While the resumption of production is crucial to social development, it elevates the risk of cluster-infections at the workplaces. Guangdong Second Provincial General Hospital therefore set up the Smart Safeguard System for COVID-19, aiming to provide rapid screening and consistent protection to assist the local enterprises with resumption. The system has received positive feedback as being helpful and practical. It has the potential to be widely used to prevent the cluster-infection of COVID-19 at workplaces during the pandemic.